Discovery of novel long non-coding RNAs induced by subgroup J avian leukosis virus infection in chicken. (November 2017) - Qiu, Lingling; Li, Zhiteng; Chang, Guobin; Bi, Yulin; Liu, Xiangping; Xu, Lu; Zhang, Yang; Zhao, Wenming; Xu, Qi; Chen, Guohong
Abstract: Avian leukosis virus subgroup J (ALV-J) is an avian oncogenic retrovirus that has led to severe economic losses in the poultry industry in China in recent decades. Here, using high throughput transcriptome sequencing of HD11 and CEF cells infected with ALV-J, a set of 4804 novel long non-coding transcripts and numerous differentially expressed long non-coding RNAs (lncRNAs) were identified. We also found that they share relatively shorter transcripts and fewer exon numbers compared to mRNA. Correlation analysis suggested that many lncRNAs may activate gene expression in an enhancer-like manner other than through transcriptional regulation. Expression level analyses in vivo showed that three lncRNAs (NONGGAT001975.2, NONGGAT005832.2 and NONGGAT009792.2) may be associated with immune response regulation and could function as novel biomarkers for ALV-J infection. Our findings provides new insight into the pathological process of ALV-J infection and should serve as a high-quality resource for further research on epigenetic influences on disease-resistance breeding as well as immune system and genomic studies. Highlights: Catalog of lncRNAs during ALV-J infection in both somatic and immune cells were provided. Functional differences in noncoding RNA regulation between them characterized for the first time. Chicken lncRNAs are shorter, have fewer exons and shorter exons than protein-coding genes. Many lncRNAs may activate gene expression in an enhancer-like manner other than transcriptional regulation. We found and validated three lncRNAs that could function as novel biomarkers for ALV-J infection.